USING KWL STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Rusmiati, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research is to improve students? reading comprehension by implementing KWL strategy to the eleventh grade students of SMA Mujahidin Pontianak. The writer conducted this project in order to solve the problems encountered in the classroom. Since it is to improve reading comprehension in learning process, the approriate technique that was applied in this research is a classroom action research. The participant of this research is the students in eleventh grade especially class XI IPA 1 of SMA Mujahidin Pontianak in Academic 2016/2017, which consists of 31 students. The data were collected by using observation method which are the achievement test, observation checklist  and field notes. There were three cycles of classroom action research process. At the first cycle, the students were still confused how to implemented KWL strategy, and many students could not fulfill the minimum score of achievement 76. At the second cycle, the students knew how to implement KWL strategy and the score was better than first cycle. And the third cycle, the students? score was better. The findings of this research indicate the students? reading comprehension mean score was 75.16, 91.62, and 99,03. Based on the result, KWL strategy can improve students? reading comprehension. Keywords : Reading Comprehension, KWL Strategy, Classroom Action Research